Pengembangan Video Pembelajaran Berbasis Aplikasi Video Scribe Pada Mata Pelajaran IPS di Sekolah Dasar - Riyanto, Muhammad; Jamaluddin, Ujang; Pamungkas, Aan Subhan (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2019)
This study aims to develop learning video based videoscribe applications on Social Science with the topic of natural phenomena. The research method used is research and development method with stages: potential and problems, data collection, product design, design validation, design revision, and product testing (limited trial). To test the feasibility of this video learning then tested the validation of experts conducted by material experts, media experts, and pedagogical experts. After the validation test by the expert team, then the product test (limited trial) with the subject of the research is the 43 students of class VI A SDN Panancangan 2. The results of the material expert test show that this video learning obtained an average score of 82.85% with the a very feasible category. The result of the media expert test shows that this video learning obtained an average score of 88.34% with a very feasible category. The results of the pedagogical expert test show this video learning obtained an average score of 85.83% with a very feasible category. The product trial results (limited trial) obtained an average grade of 90.52% with a very good category. Based on the results of this study, it can be concluded that learning video based on the application of videoscibe very feasible for use in Social Science on the topic of natural phenomenon in Indonesia.